FORM AND SYMBOLIC MEANING OF THE “SUBAMA BATIK” BATIK MOTIF BAJING KULON VILLAGE KROYA DISTRICT CILACAP REGENCY - Wahyu Haryana, Rizma (Arty: Jurnal Seni Rupa, 2025)
Batik is a cultural heritage that has deep aesthetic and symbolic value. This research aims to analyze the form and symbolic meaning of batik motifs produced by "Subama Batik", which is located in Bajing KulonVillage, Kroya District, Cilacap Regency. Subama Batik has various unique motifs and is rich in local wisdom values. This research uses a descriptive qualitative approach with data collection techniques through observation, interviews and document study. Data analysis uses data reduction, data presentation, drawing conclusions, and verification. Based on the research results, it was found that (1) The motifs produced by "Subama Batik" were inspired by flora, fauna, natural objects and life around the environment of Bajing Kulon Village, Kroya District, Cilacap Regency. The motifs created include Jambu, Ngasem, Laptu, Cassava, Nusakambangan, Srrandil, Turtle, Bamboo, Wijayakusuma, Lotus Flower, Mangrove, Hibiscus, Jellyfish, Nusakambangan Pola, Garuda Wijayakusuma, and Marine Biota motifs. (2) Every batik motif produced by "Subama Batik" has a distinctive shape and has a deep symbolic meaning, related to the culture, history and life of the surrounding community. (3) "Subama Batik" motifs, such as the Jambumotif, Ngasem motif, Laptu motif, and others, contain messages about togetherness, tolerance, historical values, and local wisdom passed down from generation to generation. This symbolic meaning is reflected in the shapes and other elements in batik, which reflect the harmonious relationship between humans, nature and local culture.